Can an incremental step test be used for maximal lactate steady state determination in swimming? Clues for practice - Espada, Mário (2021)
We aimed to compare the velocity, physiological responses, and stroke mechanics between the lactate parameters determined in an incremental step test (IST) and maximal lactate steady state (MLSS). Fourteen well-trained male swimmers (16.8 ± 2.8 years) were timed for 400 m and 200 m (T200). Afterwards, a 7 × 200-m front-crawl IST was performed. Swimming velocity, heart rate (HR), blood lactate concentration (BLC), stroke mechanics, and rate of perceived exertion (RPE) were measured throughout the IST and in the 30-min continuous test (CT) bouts for MLSS determination. Swimming velocities at lactate threshold determined with log-log methodology (1.34 ± 0.06 m·s−1) and Dmax methodology (1.40 ± 0.06 m·s−1); and also, the velocity at BLC of 4 mmol·L−1 (1.36 ± 0.07) were not significantly different from MLSSv, however, Bland–Altman analysis showed wide limits of agreement and the concordance correlation coefficient showed poor strength of agreement between the aforementioned parameters which precludes their interchangeable use. Stroke mechanics, HR, RPE, and BLC in MLSSv were not significantly different from the fourth repetition of IST (85% of T200), which by itself can provide useful support to daily practice of well-trained swimmers. Nevertheless, the determination of MLSSv, based on a CT, remains more accurate for exercise evaluation and prescription.